Victoria's Secret Symbolic Communication : Exploring the Connections Between Brand Images, Organizational Identification, and Job Satisfaction - Blunt, Courtney; Hunter, Natalie; Salentine, Angela; Cantwell, Elizabeth; Schumacher, Lindsey; Severson, Sara (My University, 2012)
The effect of advertising on consumer attitudes and behavior has been studied (Yaniv & Farkas, 2005), but less is known about how advertising may impact employees. This study examined associations between the symbolic communication of Victoria's Secret, employee perceptions of similarities with representative models used in brand advertising, and important individual and organizational outcomes.
Color poster with text, images, and graphs.
Keywords: Victoria's Secret; Employees--Attitudes; Advertising--Lingerie; Communication in marketing; Job satisfaction; Posters